Academic Service Satisfaction and UNSOED Communication Science's Reputation: Insights from Mobility Students - Wisnu Widjanarko; S Bekti Istiyanto; Edi Santoso; Wiwik Novianti; Dian Bestari; Agoeng Noegroho (Metacommunication: Journal of Communication Studies, 2024)
Indonesian National Student Mobility or Program Pertukaran Mahasiswa Merdeka (PMM) is one of the initiatives of the Ministry of Education, Culture, Research and Technology in order to improve the academic quality and diversity of students throughout Indonesia through an inter-island student exchange mechanism, either of the same type or across fields of science. Communication Studies Program at Jenderal Soedirman University (Unsoed) located in Purwokerto - Central Java, is one of those that has been mandated to receive and facilitate the program from 2022 to 2024. This research aims to identify the level of students satisfaction with the quality of academic services provided by the study program as a part of the projected reputation.  Using a descriptive approach with the SERVQUAL method on 41 respondents (PMM students), the research shows: 1) 92.5% of respondents are satisfied with choosing the Communication Studies Program at Unsoed as a destination for the national student exchange program; 2) The level of satisfaction of PMM students with the academic services provided is quite good as evidenced by the difference score between performance and expectations in the range of -0.23 to -0.06 in the aspects of reliability, assurance, responsiveness, empathy and physical evidence; 3) Expectations for learning facilities and infrastructure are the highest expectations expected by students from outside the island regarding the quality of academic facilities at the destination campus. A university's reputation is enhanced by positive student experiences, which use social media narratives rather than paid publicity to create powerful public relations.